Assessing the impact of risk perception of a community on cyclone vulnerability: A case study of Pratapnagar, Satkhira - Hasanuzzaman, A B M; Auroni, Musarrat Zaman; Fatima, Anjuman (Journal of Bangladesh Institute of Planners, 2022)
The purpose of the article is to investigate how cyclone vulnerability is triggered by a community's sense of risk. A study on this issue was conducted in Pratapnagar, Satkhira district in southern Bangladesh. The study is focused on assessing the perception of cyclone risk, the degree of adaptation of coping mechanisms, and the disparity of losses and damage resulting from the disaster. Focus group discussions and a closed-ended questionnaire survey were used in a mixed approach of study to investigate the level of the community's perception of risk and its relation to adoption of coping mechanisms and damage. The subjects were categorized in two groups. One group had a negative propensity to risk while the other had a positive inclination. The results show a significant difference in the degree of adoption and loss between these two groups. The economic losses between these two groups were considerably different. The group with negative propensity to risk needed comparatively less resources for recovery. People become oblivious to the risk of disaster due to several factors, including prior experience, a lack of trust in early warning systems, disregard for risk, etc. These results suggest that a person's risk assessment is a critical factor in determining whether they adopt the right defences to lessen the disaster's negative effects. JBIP,Vol. 15, 2022, pp. 13-24